Engaging the elderly tourists with museums - Loureiro, S.; Ferreira, E. (Proceedings of the International conference on Tourism and Ageing, 2016)
The aim of this study is to analyze the relationships among the concepts of serious leisure and meaningfulness, engagement with museums and word-of mouth among elderly tourists. We also stress the importance of being cognitive engaged with an activity and experience in order to communicate and recommend to others and even improve the cognitive healthy of elderly tourists. The structural model is tested with a sample of 263 elderly visitors (from Portugal and abroad) in a culturally specific setting of Lisbon museums (where improvements and innovations were implemented). The findings contribute to a better understanding of visitors' perceptions and valuation of museums acting as cognitive tourist attractions. Several implications can be drawn from the study findings and interesting directions for future research are provided.